The effect of Islam and science integration implementing on science learning in Indonesia: a meta-analysis - Ardi, Ardi; Lufri, Lufri; Amran, Ali; Kosasih, Ahmad; Hervi, Fauziah (Institute of Advanced Engineering and Science, 2024)
National education aims to produce dedicated, religious, moral individuals and cognitive intelligence. Applying students’ Islamic values through integrating Islam and science in science learning is one of the strategies that can be used to achieve these goals. Integrating Islam and science in science learning can direct the formation of knowledge about science concepts and improve students’ attitudes and spiritual skills. This study aims to analyze the effect of integrating Islam and science in science learning. This study explores the effect of integrating Islam and science in science learning with meta-analysis research by calculating effect size (ES). Research data were obtained from 38 studies from national and international journals. The results showed that integrating Islam and science in science learning has a significant impact, as seen from the ES of 0.658. It is explained that science learning integrating Islam and science can be an alternative learning method. Integrating Islam and science into science learning is an alternative educational method to achieve national education goals that can increase students’ intellectual and spiritual values. The results of this study can be utilized as a reference in the learning process and the development of teaching materials in science learning in the future.